Rhinosinusitis Kronis Yang Diperberat Dengan Anemia: A Case Report - Iwan Setiawan Adji; Nyovita Ayuningrum; Devy Ayu Ningtiyas; Fadli Rizal Faqihudin; Rayhan Fahrezi Al Farghani; Ria Reanita (Persatuan Dosen Kesehatan Masyarakat, 2026)
Chronic rhinosinusitis (CRS) is a ≥12-week inflammation of the paranasal sinuses influenced by anatomical and immunological factors. Iron-deficiency anemia (IDA) can worsen CRS through mucosal hypoxia, impaired ciliary function, oxidative stress, and reduced local immunity. A 15-year-old girl presented with bilateral nasal obstruction, facial pain, and difficulty clearing secretions. She had a history of heavy menstrual bleeding and showed hypochromic microcytic anemia (Hb 7.4 g/dL, serum iron 13 µg/dL, TIBC 385 µg/dL). Examination revealed bilateral inferior turbinate hypertrophy, right maxillary rhinosinusitis, and mild bilateral ethmoiditis. Inferior turbinate hypertrophy impaired sinus ventilation and drainage, leading to mucus retention and chronic inflammation. IDA further aggravated the condition by reducing mucosal oxygenation, weakening ciliary activity, and impairing phagocytic function. The patient underwent left inferior turbinate reduction first due to cross-obstruction, and received two units of PRC with gradual clinical improvement.Correction of anemia improved mucosal oxygenation and supported epithelial recovery after surgery. Overall, IDA contributes to worsening CRS, and its management is an essential component of comprehensive treatment to enhance healing and prevent recurrence.